Legal Implications of Unilateral Termination of Employment on the Protection of Workers' Rights in the Indonesian Employment System - Mehnaj Ayuda; Dinda Nurul Amalia; Maulana Sutan Hasibuan; Zulfirmansyah Rimbun; Jasni bin Sulong (ISNU Sumatera Utara, 2024)
Unilateral termination of employment (PHK) is still one of the main problems in industrial relations in Indonesia because it has the potential to ignore the normative rights of workers and cause legal uncertainty. Changes to labor regulations through Law Number 6 of 2023 concerning Job Creation are expected to be able to create a balance between the flexibility of the business world and the protection of workers, but its implementation still faces various challenges. This study aims to analyze the legal implications of unilateral termination of employment on the protection of workers' rights and examine the effectiveness of the applicable legal arrangements in the Indonesian labor system. This research is a normative legal research using a legislative approach and a conceptual approach. The legal materials used consist of primary, secondary, and tertiary legal materials that are analyzed qualitatively descriptively through deductive reasoning methods. The results of the study show that layoffs can only be carried out based on the reasons and procedures determined by laws and regulations and must be accompanied by the fulfillment of workers' rights in the form of severance pay, service award money, and other normative rights. However, the practice of unilateral layoffs still causes economic, social, and psychological losses for workers due to weak company compliance, labor supervision, and the effectiveness of law enforcement. Therefore, legal protection of workers requires more effective implementation of regulations, optimal supervision, and consistent law enforcement to ensure legal certainty and justice in industrial relations.